Pauson‐Khand Reactions with Concomitant C−O Bond Cleavage for the Preparation of 5, 5‐ 5, 6‐ and 5, 7‐Bicyclic Ring Systems. Issue 7 (16th February 2021) - Ma, Ding; Hu, Naifeng; Ao, Junli; Zang, Shaoli; Yu, Guo; Liang, Guangxin
Abstract: Pauson‐Khand reactions (PKR) with concomitant C−O bond cleavage have been developed for construction of 5, 5‐ 5, 6‐ and 5, 7‐bicyclic ring systems bearing complex stereochemistry. The chemistry generates intermolecular PKR‐type products in an absolute regio‐ and stereochemical control which is hardly achievable through real intermolecular Pauson‐Khand reactions. A mechanism for this Pauson‐Khand reaction has been proposed based on deuterium labelling experiments. Abstract :